A comparative study on solidification/stabilization characteristics of coal fly ash-based geopolymer and Portland cement on heavy metals in MSWI fly ash. (15th October 2021) - Fan, Chengcheng; Wang, Baomin; Ai, Hongmei; Qi, Yi; Liu, Ze
Abstract: Cement-based solidification/stabilization (S/S) is a widely approach applied for municipal solid waste incineration (MSWI) fly ash. Although Portland cement on MSWI fly ash S/S has been widely developed, the economical and environment-friendly binders should be explored to reduce the energy and improve MSWI fly ash S/S performances. A comparative study about MSWI fly ash S/S treatment with coal fly ash-based geopolymer and Portland cement was carried out in this work. Specifically, physical and chemical characteristics of MSWI fly ash, compressive strength, leachability and chemical speciation transformation of heavy metals, microstructures and morphology of S/S samples were investigated. Results showed that leaching concentration of Pb, Cd and Zn in MSWI fly ash was 5.36 mg/L, 40.3 mg/L and 129.0 mg/L respectively. It was 34.7, 160.2 and 0.29 times higher than Standard GB16889, far exceeding the requirements for municipal solid waste landfill. Leaching tests indicated that immobilization rates of Pb, Zn and Cd with geopolymer S/S treatment were exceeding 99%. Compressive strength of geopolymer and Portland cement S/S samples curing for 28 days varied from 14.3 to 22.4 MPa and 2.5–10.8 MPa, respectively. In summary, geopolymer exhibited better immobilization performances on MSWI fly ash than Portland cement. In geopolymer S/S samples, active aluminosilicate in MSWI fly ash participated the geopolymerization reaction and generated new phases such as Friedel' salts (3CaOAl2 O3 CaCl2 10H2 O) and hydrocalumite (Ca2 Al(OH)6 Cl2 H2 O). It not only promoted the bulk resource utilization and disposal of fly ash, but also realized the effective encapsulation of heavy metals and chloride ions. Therefore, geopolymer is a more promising candidate for MSWI fly ash S/S treatment. Graphical abstract: Image 1 Highlights: Comparative study of geopolymer and Portland cement on MSWI fly ash was conducted. Geopolymer indicated a higher immobilization ratio on Zn, Pb, and Cd, up to 99%. Main heavy metals transformed into the stable forms difficult to leach out. Geopolymer is superior to Portland cement on MSWI fly ash immobilization.